Resistance of European ash (Fraxinus excelsior) saplings to larval feeding by the emerald ash borer (Agrilus planipennis). Issue 1 (13th November 2019) - Showalter, David N.; Saville, Robert J.; Orton, Elizabeth S.; Buggs, Richard J. A.; Bonello, Pierluigi; Brown, James K. M.
Societal Impact Statement: European ash is a significant tree commercially, ecologically, and culturally. It is currently threatened by two invasive species, the fungus that causes ash dieback and the emerald ash borer (EAB) beetle. We show that saplings of European ash are much less susceptible to EAB than black ash, which has suffered severe damage in North America, but have similar resistance to Manchurian ash, which coexists with EAB in East Asia. Selecting ash with stronger resistance to dieback is unlikely to decrease its resistance to EAB. As we do not know what the combined effect of ash dieback and EAB will be on European ash, biosecurity measures are needed to exclude EAB from Western Europe. Abstract : European ash is threatened by two invasive species, the fungus which causes ash dieback and a beetle, the emerald ash borer (EAB). Saplings of European ash are much less susceptible to EAB than black ash, which has suffered severe damage in North America, but have similar resistance to Manchurian ash, which coexists with EAB in East Asia. Selecting ash with stronger resistance to dieback is unlikely to decrease its resistance to EAB. As we do not know what the combined effect of ash dieback and EAB will be on European ash, biosecurity measures are needed to exclude EAB from Western Europe.